2012
DOI: 10.1039/c2jm32322b
|View full text |Cite
|
Sign up to set email alerts
|

The protein resistance of silicones prepared with a PEO-silane amphiphile

Abstract: Silicone coatings with improved resistance to plasma proteins were prepared by incorporating a PEOsilane amphiphile: a-(EtO) 3 Si-(CH 2 ) 2 -oligodimethylsiloxane 13 -block-poly(ethylene oxide) 8 -OCH 3 . The oligodimethylsiloxane tether imparts amphiphilicity and molecular mobility to the chain thereby enhancing protein resistance. Using a medical grade, silica-filled acetoxy-cure silicone, the PEO-silane amphiphile was introduced at varying levels (0, 1, 5, 10, 15 and 20 wt%) and films prepared via solventca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 39 publications
2
47
0
Order By: Relevance
“…The water-driven restructuring of PEO to the surface of such bulk-modified silicones has been directly observed [47]. In addition, temporally measuring the θ static of a deposited water droplet has been shown to effectively monitor reorganization of PEO to the surface-water interface [4446]. Therefore, the 15 bulk-modified silicones and unmodified silicone control (0.14 ± 0.01 mm thick by electronic caliper) were evaluated by measuring θ static of water droplets over a 5 min period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The water-driven restructuring of PEO to the surface of such bulk-modified silicones has been directly observed [47]. In addition, temporally measuring the θ static of a deposited water droplet has been shown to effectively monitor reorganization of PEO to the surface-water interface [4446]. Therefore, the 15 bulk-modified silicones and unmodified silicone control (0.14 ± 0.01 mm thick by electronic caliper) were evaluated by measuring θ static of water droplets over a 5 min period.…”
Section: Resultsmentioning
confidence: 99%
“…Adsorbed fibrinogen plays a well-established role in the initiation of surface-induced thrombosis [49,50] and is commonly used to evaluate material thrombogenicity in vitro [14,27,34,46,47,51]. Oeveren et al concluded that fibrinogen adsorption was one of the most reliable methods to predict thrombogenicity for many materials [52].…”
Section: Resultsmentioning
confidence: 99%
“…61-66 Its use in evaluating the thromboresistance of materials in vitro has also been well established. 26, 40, 46-49, 53, 54, 63, 67-71 Adsorption of HF onto surface-grafted silicon wafers was measured by quartz crystal microbalance with dissipation monitoring (QCM-D) (Figure 4). QCM-D has been widely used for measuring adsorption of proteins on low-fouling grafted monolayers and thin films.…”
Section: Resultsmentioning
confidence: 99%
“…44, 46, 48, 49 Adsorption of fluorescently-labeled HF (100 μg/mL) was measured on silicone in terms of absolute fluorescent intensity (Table S3) and that normalized to unmodified silicone (Figure 7). The unmodified silicone, due to its high hydrophobicity, resulted in characteristically high protein adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…Bulk-modification of a silica-reinforced silicone with PEO-silane amphiphile ( m = 13) likewise demonstrated water-driven surface-restructuring and protein resistance. 32 Atomic force microscopy (AFM) analysis verified that PEO segments of the PEO-silane amphiphile ( m = 13) were driven to the surface-water interface of the silicone. 33 In this way, PEO-silane amphiphiles functioned as effective “surface-modifying additives” (SMAs) 34 for silicones.…”
Section: Introductionmentioning
confidence: 97%